National Needs Assessment of Utilization of Common Newborn Clinical Decision Support Tools - Beam, Kristyn; Wang, Cindy; Beam, Andrew; Clark, Reese; Tolia, Veeral; Ahmad, Kaashif (American Journal of Perinatology, 2023)
Objective Clinical decision support tools (CDSTs) are common in neonatology, but utilization is rarely examined. We examined the utilization of four CDSTs in newborn care.Study Design A 72-field needs assessment was developed. It was distributed to listservs encompassing trainees, nurse practitioners, hospitalists, and attendings. At the conclusion of data collection, responses were downloaded and analyzed.Results We received 339 fully completed questionnaires. BiliTool and the Early-Onset Sepsis (EOS) tool were used by > 90% of respondents, the Bronchopulmonary Dysplasia tool by 39%, and the Extremely Preterm Birth tool by 72%. Common reasons CDSTs did not impact clinical care included lack of electronic health record integration, lack of confidence in prediction accuracy, and unhelpful predictions.Conclusion From a national sample of neonatal care providers, there is frequent but variable use of four CDSTs. Understanding the factors that contribute to tool utility is vital prior to development and implementation.Key Points
Keywords: neonatology; clinical decision support; machine learning; electronic health records; health informatics